Autoantibodies in the diagnostic work-up of neuropathy: clinically useful or purely academic?. (2nd July 2020) - Sahi, Nitin; Ghasemi, Majid; Rajabally, Yusuf A
Abstract : The search for autoantibodies in patients with acute and chronic neuropathies has become widespread in neurological practice. These tests are more routinely available and therefore are more commonly requested in larger hospitals with neuroscience centres, although they are now also regularly requested from district general hospital settings, including by non-neurologists. However, the clinical value of these frequently expensive tests is often unclear and their impact on management not always obviously beneficial. This article reviews the main immunological tests used to search for specific autoantibodies in the setting of neuropathy and discusses their potential diagnostic importance, together with the eventual therapeutic implications of results obtained.